Cell wall proteomic of Brachypodium distachyon grains: A focus on cell wall remodeling proteins. Issue 13 (27th April 2015) - Francin‐Allami, Mathilde; Merah, Kahina; Albenne, Cécile; Rogniaux, Hélène; Pavlovic, Marija; Lollier, Virginie; Sibout, Richard; Guillon, Fabienne; Jamet, Elisabeth; Larré, Colette
<x xml:space="preserve">Abstract</x> Cell walls play key roles during plant development. Following their deposition into the cell wall, polysaccharides are continually remodeled according to the growth stage and stress environment to accommodate cell growth and differentiation. To date, little is known concerning the enzymes involved in cell wall remodeling, especially in gramineous and particularly in the grain during development. Here, we investigated the cell wall proteome of the grain of Brachypodium distachyon. This plant is a suitable model for temperate cereal crops. Among the 601 proteins identified, 299 were predicted to be secreted. These proteins were distributed into eight functional classes; the class of proteins that act on carbohydrates was the most highly represented. Among these proteins, numerous glycoside hydrolases were found. Expansins and peroxidases, which are assumed to be involved in cell wall polysaccharide remodeling, were also identified. Approximately half of the proteins identified in this study were newly discovered in grain and were not identified in the previous proteome analysis conducted using the culms and leaves of B. distachyon. Therefore, the data obtained from all organs of B. distachyon infer a global cell wall proteome consisting of 460 proteins. At present, this is the most extensive cell wall proteome of a monocot species.